Antimicrobial studies, synthesis and characterization of novel 1-nitro-10H-phenothiazine bearing sulfone/nucleoside moieties. (3rd August 2019) - Jangid, Dinesh Kumar; Guleria, Anjali; Gautam, Dinesh C.; Yadav, Hemendra; Mathur, Manas; Swami, Ajit Kumar
Abstract: The current research article involves one pot synthesis of novel substituted 1-nitro-10 H- phenothiazines via Smiles rearrangement. These substituted phenothiazines undergo oxidation to yield 10 H -phenothiazine-5, 5-dioxides (sulfones) while on treatment with β-D-ribofuranose-1-acetate-2, 3, 5-tribenzoate yield ribofuranosides. These compounds were screened for their antimicrobial vitalities ( in vitro ) against selected strains of bacteria and fungi. The characterization of synthesized compounds was done by elemental and spectral studies. GRAPHICAL ABSTRACT: